2013
DOI: 10.1016/j.bbrc.2013.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Functional inhibition of UQCRB suppresses angiogenesis in zebrafish

Abstract: As a subunit of mitochondrial complex III, UQCRB plays an important role in complex III stability, electron transport, and cellular oxygen sensing. Herein, we report UQCRB function regarding angiogenesis in vivo with the zebrafish (Danio rerio). UQCRB knockdown inhibited angiogenesis in zebrafish leading to the suppression of VEGF expression. Moreover, the UQCRB-targeting small molecule terpestacin also inhibited angiogenesis and VEGF levels in zebrafish, supporting the role of UQCRB in angiogenesis. Collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Another oxidative phosphorylation-related DEG, UQCRB, encodes subunit 7 of ubiquinol cytochrome c reductase. UQCRB plays a key role in hypoxia-induced angiogenesis and mitochondria-mediated metabolic disorders (Jung et al 2011;Chang et al 2014;Chang et al 2015), and the loss of UQCRB function inhibits angiogenesis (Cho et al 2013). NDUFS6 encodes NADH, ubiquinone oxidoreductase and dehydrogenase (ubiquinone) Fe-S protein 6 (Loeffen et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Another oxidative phosphorylation-related DEG, UQCRB, encodes subunit 7 of ubiquinol cytochrome c reductase. UQCRB plays a key role in hypoxia-induced angiogenesis and mitochondria-mediated metabolic disorders (Jung et al 2011;Chang et al 2014;Chang et al 2015), and the loss of UQCRB function inhibits angiogenesis (Cho et al 2013). NDUFS6 encodes NADH, ubiquinone oxidoreductase and dehydrogenase (ubiquinone) Fe-S protein 6 (Loeffen et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, pyridaben, fenpyroxymate, tebufenpyrad, and rotenone inhibit Complex I of the electron transport chain, while pyraclostrobin and trifloxystrobin inhibit respiratory Complex III. Corroborating the importance of Complex III for angiogenesis, knock down or chemical inhibition of ubiquinol-cytochrome c reductase binding protein (Uqcrb), a Complex III subunit, in zebrafish inhibits ISV angiogenesis and suppresses VEGF levels [64]. It should be noted that inhibition of mitochondrial function is a relatively common mechanism of action for pesticides, and the correlation between mitochondrial disruptive activity and high VDC ranking might be ancillary.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies revealed that terpestacin suppresses angiogenesis by inhibiting the generation of ROS by complex III during hypoxia. The loss of the ROS signal in turn limits the hypoxia-induced stabilization of HIF-1α, a transcriptional driver of VEGF expression and angiogenesis 107 . At concentrations that suppress ROS generation, terpestacin did not inhibit cellular respiration or ATP generation.…”
Section: Further Evidence For Complex Iii-derived Ros In O2 Sensingmentioning
confidence: 99%